Sanitary situation of Aleppo pine and holm oak on the Sidi R'Ghies forest, Algeria - MALIKA RACHED-KANOUNI; ZAHIA KADI; Hichem Khammar; RATIBA BOUSBA; ROMAISSA AMRANE; BESMA CHELLAL; LABED ABABSA (Society for Indonesian Biodiversity, 2020)
Abstract. Rached-Kanouni M, Kadi Z, Khammar H, Bousba R, Amrane R, Chellal B, Ababsa L. 2020. Sanitary situation of Aleppo pine and holm oak on the Sidi R'Ghies forest, Algeria. Biodiversitas 21: 3954-3960. The present work aims to assess the vitality status of the Sidi R'Ghies forest and its evolution over time. Eight plots (4 plots for Aleppo pine and 4 for holm oak) were selected at random. The data collected on sample trees are analyzed using two methods: ARCHI, which is based on a reading of the tree architecture, and the assessment of biodiversity using the potential biodiversity index (PBI). The diagnostic results show that the majority of these plots are subject to climatic, pedological, and anthropogenic stresses and their health status is quite low. Despite the pressures and threats to the massif, it remains viable. But this potential is insufficient. To this end, silvicultural interventions are necessary to ensure the viability of this ecosystem by promoting the regeneration of species differences and to include a permanent ecological monitoring system.